FRI0403 CLINICAL FEATURES OF PROSTHETIC JOINT INFECTIONS DIFFER IN PATIENTS WITH INFLAMMATORY ARTHRITIS AND OSTEOARTHRITIS. (2nd June 2020) - Kapadia, M.; Pannellini, T.; Moezinia, C.; Miller, A.; Figgie, M.; Sculco, P.; Cross, M.; Henry, M.; Russell, L.; Donlin, L.; Nocon, A.; Goodman, S.
Abstract : Background: Inflammatory arthritis (IA) patients are at increased risk for prosthetic joint infections (PJI). However, because active IA patients without infections can have elevated inflammatory markers that mimic joint infection, PJI diagnosis is challenging in this population. Objectives: We used an institutional PJI registry to identify and compare the clinical, microbiologic, and histopathologic features of culture positive (CP) and culture negative (CN) total hip and knee PJI in IA and OA patients. We also evaluated the relationship between culture positivity, IA, and clinical outcomes. Methods: A retrospective cohort of THA/TKA PJIs, from 2009 to 2016, were identified by ICD codes, and confirmed by chart review. IA diagnosis was also confirmed by use of IA-specific medications. CN cases were defined as PJIs with no evidence of microbial growth in intraoperative cultures and CP PJI cases were defined by positive microbial growth in intraoperative cultures. Treatment failure was defined as subsequent surgical treatment for infection after the initial infection surgery. H&E slides of OA and IA PJI cases matched by age (+/-5) sex, and culture status were reviewed by a pathologist for evidence of the histopathologic features listed in Table 2 . Fisher's exact test, chi-square test, and Kaplan-Meier estimates were used. Results: 807 PJI cases were identified including 36 IA (33 RA and 3 SLE) and 771 OA. A higher proportion of IA PJI were CN (N=10, 27%) vs. OA PJI (N=109, 14%, p=0.02). IA-PJI were younger, female, on glucocorticoids, and with more comorbidities. Type of surgical treatment did not differ significantly between IA and OA groups. Comparing CN-IA vs. CP-IA, no difference was observed in age, smoking, diabetes, surgical treatment, IA-specific meds or Charlson comorbidities. One-year survivorship of CN-IA and CN-OA were 66% and 87% (p>0.05). Across all CP cases, 57% were staphylococcal, with no differences between groups. Treatment failure was more frequent for CP-IA (42%) compared to CP-OA (30%), (p=0.2). Histopathology of 88 PJIs (31 IA and 57 OA) was reviewed. The IA cohort presented with more chronic inflammation (p=0.001) than the OA cohort. Within the IA cohort, a higher proportion of CP-IA had >10PMN per HPF (p= 0.003) and met MSIS criteria (p=0.009). Comparing CP-OA and CN-OA, there were no significant differences in histopathology findings or number of patients meeting MSIS criteria. Conclusion: IA PJIs are more likely to be culture negative than OA PJIs. Although our analysis was limited by our cohort size, our findings including differences in histopathology, and better clinical outcomes suggest the presence of biologic differences between CN and CP PJI that require further study. Disclosure of Interests: Milan Kapadia: None declared, Tania Pannellini: None declared, Carine Moezinia: None declared, Andy Miller: None declared, Mark Figgie: None declared, Peter Sculco: None declared, Michael Cross: None declared, Michael Henry: None declared, Linda Russell: None declared, Laura Donlin Consultant of: Consultant – Genentech/Roche, Allina Nocon: None declared, Susan Goodman Shareholder of: Reginosine- Investment, Grant/research support from: Novartis, Horizon, Consultant of: Novartis, Celgene, UCB